ChemInform Abstract: Design Strategies, Structure Activity Relationship and Mechanistic Insights for Purines as Kinase Inhibitors. Issue 16 (March 2016) - Sharma, Sahil; Singh, Jagjeet; Ojha, Ritu; Singh, Harbinder; Kaur, Manpreet; Bedi, P. M. S.; Nepali, Kunal
Abstract: Review: 212 refs.